2014
DOI: 10.1007/978-1-4614-3185-5
|View full text |Cite
|
Sign up to set email alerts
|

Handbook of Research on Educational Communications and Technology

Abstract: pointers to exemplary work that has implications for research in educational communications and technology. This part of the Handbook consists of seven chapters covering: (1) historical foundations, (2) theoretical foundations, (3) complexity theory, (4) experiential perspectives, (5) empirical perspectives, (6) contextualistic perspectives, and (7) philosophical perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(100 citation statements)
references
References 7 publications
2
90
0
8
Order By: Relevance
“…Similar to other subjects which are disseminated by teachers, the integration of ICT into teaching and learning processes requires teachers to acquire a certain level of different skills to handle all challenges attached to the integration of ICT into teaching and learning processes (Igbo & Imo, 2017). The theoretical framework of Technological Pedagogical Content Knowledge (TPACK) was introduced for understanding the teachers' knowledge required for integrating ICT into teaching and learning processes (Koehler et al, 2014;Koehler, 2006 andSchmidt et al, 2008). Figure 2, teachers require different knowledge for better integrating ICT into teaching and learning processes (Mishra & Koehler, 2006;Schmidt et al, 2008;Koeher et al, 2014).…”
Section: What Are the Skills Required For Integration Ict In Teachingmentioning
confidence: 99%
“…Similar to other subjects which are disseminated by teachers, the integration of ICT into teaching and learning processes requires teachers to acquire a certain level of different skills to handle all challenges attached to the integration of ICT into teaching and learning processes (Igbo & Imo, 2017). The theoretical framework of Technological Pedagogical Content Knowledge (TPACK) was introduced for understanding the teachers' knowledge required for integrating ICT into teaching and learning processes (Koehler et al, 2014;Koehler, 2006 andSchmidt et al, 2008). Figure 2, teachers require different knowledge for better integrating ICT into teaching and learning processes (Mishra & Koehler, 2006;Schmidt et al, 2008;Koeher et al, 2014).…”
Section: What Are the Skills Required For Integration Ict In Teachingmentioning
confidence: 99%
“…Nevertheless, the differences that set them apart can also bring them together. (Wasserman, 2007) According to Oh & Reeves (2011), the generational differences are widely discussed in the popular press, business-oriented books, conferences, workshops and so on. The terminology used to label the generations is not standardized because various people writing about generational differences have come up with a variety of different names to label the various generations.…”
Section: Literature and Theoretical Backgroundmentioning
confidence: 99%
“…Mishra and Koehler (2006) and Koehler and Mishra (2009) further added the combination and intersections of these components as technological pedagogical knowledge (TPK), pedagogical content knowledge (PCK), and technological content knowledge (TCK). Koehler, Mishra, Kereluik, Shin, and Graham (2014) indicate that numerous instruments were developed to assess pre-and in-service teachers within the TPACK framework but only 66 research publications met the inclusion criteria among 303 TPACK related articles. From those research articles, 141 instruments of various types were found.…”
Section: New Perspective On Tpack Framework In the Context Of Early Cmentioning
confidence: 99%
“…The subcategories for affective were the five levels of affective domain taxonomy (Krathwohl et al, 1964;Krathwohl, 2002) and additional codings collectively clustered under "other" subcategory. The subcategories for TPACK consisted of the seven components in the TPACK framework (Koehler et al, 2014) with additional attention to technology related components divided up into iPad technology and general technology.…”
Section: First Cycle Codingmentioning
confidence: 99%